Venous Thromboembolism Risk With JAK Inhibitors: A Meta‐Analysis. Issue 5 (25th March 2021) - Yates, Mark; Mootoo, Amanda; Adas, Maryam; Bechman, Katie; Rampes, Sanketh; Patel, Vishit; Qureshi, Sumera; Cope, Andrew P.; Norton, Sam; Galloway, James B.
Abstract : Objective: JAK inhibitor therapies are effective treatment options for immune‐mediated inflammatory diseases (IMIDs), but their use has been limited by venous thromboembolism (VTE) risk warnings from licensing authorities. We undertook this study to evaluate the VTE risk of JAK inhibitors in patients with IMIDs. Methods: Systematic searches of Medline and Embase databases from inception to September 30, 2020 were conducted. Phase II and phase III double‐blind, randomized controlled trials (RCTs) of JAK inhibitors at licensed doses were included in our analyses. RCTs with no placebo arm, long‐term extension studies, post hoc analyses, and pooled analyses were excluded. Three researchers independently extracted data on exposure to JAK inhibitors or placebo and VTE events (e.g., pulmonary embolism [PE] and deep vein thrombosis [DVT]) and assessed study quality. Results: A total of 42 studies were included, from an initial search that yielded 619. There were 6, 542 JAK inhibitor patient exposure years (PEYs) compared to 1, 578 placebo PEYs. There were 15 VTE events in the JAK inhibitor group and 4 in the placebo group. The pooled incidence rate ratios (IRRs) of VTE, PE, and DVT in patients receiving JAK inhibitors were 0.68 (95% confidence interval [95% CI] 0.36–1.29), 0.44 (95% CI 0.28–0.70), and 0.59 (95% CI 0.31–1.15), respectively. Conclusion: This meta‐analysis of RCT data defines the VTE risk with JAK inhibitors as a class in IMID patients. The pooled IRRs do not provide evidence that support the current warnings of VTE risk for JAK inhibitors. These findings will aid continued development of clinical guidelines for the use of JAK inhibitors in IMIDs.